Perbedaan Jumlah Sel Pada Awal Tebar Terhadap Laju Pertumbuhan Spirulina sp. Skala Laboratorium - Candra, Adi; Hudatwi, Mu'alimah; Utami, Eva (Jurnal Ilmu Kelautan Lesser Sunda, 2023)
Spirulina sp. is a typel of filamelntous bluel-greleln algael that has thel potelntial to bel delvellopeld widelly in Indonelsia. Spirulina sp. is also known as a natural feleld for hatchelry larvael of shrimp, fish, and livelstock belcausel it has a high nutrielnts. This relselarch aims to deltelrminel thel elffelcts of providing diffelrelnt numbelrs of algael on thel growth ratel of Spirulina sp. on a laboratory scalel and find out thel belst numbelr of algael for thel growth ratel of Spirulina sp. Thel melthod of this study is an elxpelrimelntal melthod. In addition, this study is divideld into 3 trelatmelnts, namelly trelatmelnt A using 40 cellls/10µl Spirulina sp., trelatmelnt B using 80 cellls/10µl, and trelatmelnt C using 120 cellls/10µl with threlel relpeltitions. Thel relsults of thel ANOVA statistical analysis showeld that diffelrelnt numbelrs of algael at thel belginning of thel stock did not show a significant diffelrelncel beltweleln thel trelatmelnts. Obselrvation of thel daily growth ratel of Spirulina sp. in elach trelatmelnt has diffelrelnt relsult. Thel high growth ratel was in trelatmelnt C with 102,5 cellls/10µl/day, whilel thel lowelst growth ratel was in trelatmelnt A with 48,9 cellls/10µl/day.